Life-Cycle Health Risk and Environmental Burden Assessment of Reusable vs Single-Use Medical Textiles: An Innovative Comparison of Worker Exposure and Carbon Emissions - Ulin Nafiah; Yeni Rusyani; Trinkul Kalita (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
The healthcare industry is increasingly relying on medical textiles, particularly single-use items such as surgical gowns, masks, and drapes, to maintain hygiene and prevent infections. However, the widespread use of these single-use textiles raises significant environmental and health concerns. These items are primarily made from non-biodegradable materials, contributing to large volumes of waste and environmental pollution. The production and disposal of single-use textiles also generate carbon emissions, further exacerbating climate change. In response to these challenges, reusable medical textiles have emerged as a more sustainable alternative. Reusable textiles offer several environmental benefits, including reduced resource consumption, lower carbon emissions, and decreased waste generation. Additionally, reusable textiles can improve occupational health by reducing healthcare workers' exposure to harmful chemicals and irritants found in single-use textiles. This study compares the environmental impact and occupational health risks associated with reusable and single-use medical textiles, focusing on factors such as carbon footprint, waste generation, and chemical exposure. Life-cycle assessment (LCA) methodologies were employed to quantify the environmental impacts, while workplace exposure measurements assessed the health risks to healthcare workers. The results indicate that reusable textiles significantly reduce carbon emissions and waste compared to single-use textiles. Furthermore, reusable textiles were associated with lower levels of chemical exposure for healthcare workers. The study concludes with recommendations for healthcare systems to adopt reusable textiles to reduce environmental and health risks, while also suggesting areas for future research on sustainable textile innovations and the integration of reusable systems in healthcare facilities.